Activated carbon as catalyst support: precursors, preparation, modification and characterization - Iwanow, Melanie; Gärtner, Tobias; Sieber, Volker; König, Burkhard (Beilstein Journal of Organic Chemistry, 2020)
The preparation of activated carbon materials is discussed along selected examples of precursor materials, of available production and modification methods and possible characterization techniques. We evaluate the preparation methods for activated carbon materials with respect to its use as catalyst support and identify important parameters for metal loading. The considered carbon sources include coal, wood, agricultural wastes or biomass as well as ionic liquids, deep eutectic solvents or precursor solutions. The preparation of the activated carbon usually involves pre-treatment steps followed by physical or chemical activation and application dependent modification. In addition, highly porous materials can also be produced by salt templating or ultrasonic spray pyrolysis as well as by microwave irradiation. The resulting activated carbon materials are characterized by a variety of techniques such as SEM, FTIR, nitrogen adsorption, Boehm titrations, adsorption of phenol, methylene blue and iodine, TPD, CHNS/O elemental analysis, EDX, XPS, XRD and TGA.
Keywords: activated carbon; catalysis; characterization techniques; metal supported on carbon catalysts; preparation methods

(untitled) - Auer, E.; Freund, A.; Pietsch, J.; Tacke, T. (Appl. Catal., A, 1998)

Carbon Materials for Catalysis - Rodŕíguez‐Reinoso, F.; Seṕulveda‐Escribano, A. (Carbon as Catalyst Support, 2008)

(untitled) - Alslaibi, T. M.; Abustan, I.; Ahmad, M. A.; Foul, A. A. (J. Chem. Technol. Biotechnol., 2013)

(untitled) - Munoz-Guillena, M. J.; Illan-Gomez, M. J.; Martin-Martinez, J. M.; Linares-Solano, A.; Salinas-Martinez de Lecea, C. (Energy Fuels, 1992)

(untitled) - Pietrzak, R.; Wachowska, H.; Nowicki, P. (Energy Fuels, 2006)

(untitled) - Hsu, L.-Y.; Teng, H. (Fuel Process. Technol., 2000)

(untitled) - Yang, J.; Yue, L.; Lin, B.; Wang, L.; Zhao, Y.; Lin, Y.; Chang, K.; DaCosta, H.; Hu, X. (Energy Fuels, 2017)

(untitled) - Lillo-Ródenas, M. A.; Cazorla-Amorós, D.; Linares-Solano, A. (Carbon, 2003)

(untitled) - Perrin, A.; Celzard, A.; Albiniak, A.; Kaczmarczyk, J.; Marêché, J. F.; Furdin, G. (Carbon, 2004)

(untitled) - Pietrzak, R. (Fuel, 2009)

(untitled) - Pietrzak, R.; Jurewicz, K.; Nowicki, P.; Babeł, K.; Wachowska, H. (Fuel, 2007)

(untitled) - Pietrzak, R.; Wachowska, H.; Nowicki, P.; Babeł, K. (Fuel Process. Technol., 2007)

(untitled) - Lillo-Ródenas, M. A.; Cazorla-Amorós, D.; Linares-Solano, A.; Béguin, F.; Clinard, C.; Rouzaud, J. N. (Carbon, 2004)

(untitled) - Lillo-Ródenas, M. A.; Juan-Juan, J.; Cazorla-Amorós, D.; Linares-Solano, A. (Carbon, 2004)

(untitled) - Khezami, L.; Chetouani, A.; Taouk, B.; Capart, R. (Powder Technol., 2005)

(untitled) - Suhas; Gupta, V. K.; Carrott, P. J. M.; Singh, R.; Chaudhary, M.; Kushwaha, S. (Bioresour. Technol., 2016)

(untitled) - Suhas; Carrott, P. J. M.; Ribeiro Carrott, M. M. L. (Bioresour. Technol., 2007)

(untitled) - Foo, K. Y.; Hameed, B. H. (Bioresour. Technol., 2012)

(untitled) - Ioannidou, O.; Zabaniotou, A. (Renewable Sustainable Energy Rev., 2007)

(untitled) - Jain, A.; Balasubramanian, R.; Srinivasan, M. P. (Chem. Eng. J., 2016)

(untitled) - Hoseinzadeh Hesas, R.; Wan Daud, W. M. A.; Sahu, J. N.; Arami-Niya, A. (J. Anal. Appl. Pyrolysis, 2013)

(untitled) - Yahya, M. A.; Al-Qodah, Z.; Ngah, C. W. Z. (Renewable Sustainable Energy Rev., 2015)

(untitled) - Chen, Y.; Zhu, Y.; Wang, Z.; Li, Y.; Wang, L.; Ding, L.; Gao, X.; Ma, Y.; Guo, Y. (Adv. Colloid Interface Sci., 2011)

(untitled) - González-García, P. (Renewable Sustainable Energy Rev., 2018)

(untitled) - Li, X.; Han, C.; Chen, X.; Shi, C. (Microporous Mesoporous Mater., 2010)

(untitled) - Gao, P.; Liu, Z.-h.; Xue, G.; Han, B.; Zhou, M.-h. (Bioresour. Technol., 2011)

(untitled) - Fierro, V.; Muñiz, G.; Basta, A. H.; El-Saied, H.; Celzard, A. (J. Hazard. Mater., 2010)

(untitled) - Miao, Q.; Tang, Y.; Xu, J.; Liu, X.; Xiao, L.; Chen, Q. (J. Taiwan Inst. Chem. Eng., 2013)

(untitled) - Qin, C.; Chen, Y.; Gao, J.-m. (Mater. Lett., 2014)

(untitled) - Kalderis, D.; Bethanis, S.; Paraskeva, P.; Diamadopoulos, E. (Bioresour. Technol., 2008)

(untitled) - Malik, P. K. (Dyes Pigm., 2003)

(untitled) - Yalçın, N.; Sevinç, V. (Carbon, 2000)

(untitled) - Le Van, K.; Luong Thi, T. T. (Prog. Nat. Sci.: Mater. Int., 2014)

(untitled) - Demiral, H.; Gündüzoğlu, G. (Bioresour. Technol., 2010)

(untitled) - Valix, M.; Cheung, W. H.; McKay, G. (Chemosphere, 2004)

(untitled) - Bernardo, E. C.; Egashira, R.; Kawasaki, J. (Carbon, 1997)

(untitled) - Cronje, K. J.; Chetty, K.; Carsky, M.; Sahu, J. N.; Meikap, B. C. (Desalination, 2011)

(untitled) - Michel, R.; Mischler, N.; Azambre, B.; Finqueneisel, G.; Machnikowski, J.; Rutkowski, P.; Zimny, T.; Weber, J. V. (Environ. Chem. Lett., 2006)

(untitled) - Shim, T.; Yoo, J.; Ryu, C.; Park, Y.-K.; Jung, J. (Bioresour. Technol., 2015)

(untitled) - Liu, Q.-S.; Zheng, T.; Wang, P.; Guo, L. (Ind. Crops Prod., 2010)

(untitled) - Hameed, B. H.; Din, A. T. M.; Ahmad, A. L. (J. Hazard. Mater., 2007)

(untitled) - Yang, C.-S.; Jang, Y. S.; Jeong, H. K. (Curr. Appl. Phys., 2014)

(untitled) - Jieying, Z.; Zhao, Q.; Ye, Z. (Appl. Surf. Sci., 2014)

(untitled) - Deng, H.; Zhang, G.; Xu, X.; Tao, G.; Dai, J. (J. Hazard. Mater., 2010)

(untitled) - Şahin, Ö.; Saka, C. (Bioresour. Technol., 2013)

(untitled) - Saka, C. (J. Anal. Appl. Pyrolysis, 2012)

(untitled) - Ahmadpour, A.; Do, D. D. (Carbon, 1997)

(untitled) - Lua, A. C.; Yang, T. (J. Colloid Interface Sci., 2004)

(untitled) - Pietrzak, R.; Nowicki, P.; Kaźmierczak, J.; Kuszyńska, I.; Goscianska, J.; Przepiórski, J. (Chem. Eng. Res. Des., 2014)

(untitled) - Şentorun-Shalaby, Ç. d.; Uçak-Astarlıogˇlu, M. G.; Artok, L.; Sarıcı, Ç. (Microporous Mesoporous Mater., 2006)

(untitled) - Aygün, A.; Yenisoy-Karakaş, S.; Duman, I. (Microporous Mesoporous Mater., 2003)

(untitled) - Nowicki, P.; Kazmierczak, J.; Pietrzak, R. (Powder Technol., 2015)

(untitled) - Bouchelta, C.; Medjram, M. S.; Bertrand, O.; Bellat, J.-P. (J. Anal. Appl. Pyrolysis, 2008)

(untitled) - Uçar, S.; Erdem, M.; Tay, T.; Karagöz, S. (Appl. Surf. Sci., 2009)

(untitled) - Al Bahri, M.; Calvo, L.; Gilarranz, M. A.; Rodriguez, J. J. (Chem. Eng. J., 2012)

(untitled) - Okman, I.; Karagöz, S.; Tay, T.; Erdem, M. (Appl. Surf. Sci., 2014)

(untitled) - Fernandez, M. E.; Nunell, G. V.; Bonelli, P. R.; Cukierman, A. L. (Ind. Crops Prod., 2014)

(untitled) - Prahas, D.; Kartika, Y.; Indraswati, N.; Ismadji, S. (Chem. Eng. J., 2008)

(untitled) - Foo, K. Y.; Hameed, B. H. (Microporous Mesoporous Mater., 2012)

(untitled) - Prauchner, M. J.; Rodríguez-Reinoso, F. (Microporous Mesoporous Mater., 2012)

(untitled) - Hu, Z.; Srinivasan, M. P. (Microporous Mesoporous Mater., 1999)

(untitled) - Tan, Y. L.; Islam, M. A.; Asif, M.; Hameed, B. H. (Energy, 2014)

(untitled) - Yue, L.; Xia, Q.; Wang, L.; Wang, L.; DaCosta, H.; Yang, J.; Hu, X. (J. Colloid Interface Sci., 2018)

(untitled) - Román, S.; González, J. F.; González-García, C. M.; Zamora, F. (Fuel Process. Technol., 2008)

(untitled) - Yakout, S. M.; Sharaf El-Deen, G. (Arabian J. Chem., 2016)

(untitled) - Martínez, M. L.; Torres, M. M.; Guzmán, C. A.; Maestri, D. M. (Ind. Crops Prod., 2006)

(untitled) - Foo, K. Y.; Hameed, B. H. (Bioresour. Technol., 2011)

(untitled) - Deng, S.; Hu, B.; Chen, T.; Wang, B.; Huang, J.; Wang, Y.; Yu, G. (Adsorption, 2015)

(untitled) - Boonamnuayvitaya, V.; Sae-ung, S.; Tanthapanichakoon, W. (Sep. Purif. Technol., 2005)

(untitled) - Lamine, S. M.; Ridha, C.; Mahfoud, H.-M.; Mouad, C.; Lotfi, B.; Al-Dujaili, A. H. (Energy Procedia, 2014)

(untitled) - Song, M.; Jin, B.; Xiao, R.; Yang, L.; Wu, Y.; Zhong, Z.; Huang, Y. (Biomass Bioenergy, 2013)

(untitled) - El-Hendawy, A.-N. A. (Carbon, 2003)

(untitled) - Adinata, D.; Wan Daud, W. M. A.; Aroua, M. K. (Bioresour. Technol., 2007)

(untitled) - Tan, I. A. W.; Ahmad, A. L.; Hameed, B. H. (Desalination, 2008)

(untitled) - Guo, J.; Lua, A. C. (Microporous Mesoporous Mater., 1999)

(untitled) - Yue, L.; Rao, L.; Wang, L.; Wang, L.; Wu, J.; Hu, X.; DaCosta, H.; Yang, J.; Fan, M. (Ind. Eng. Chem. Res., 2017)

(untitled) - Zhang, S.; Miran, M. S.; Ikoma, A.; Dokko, K.; Watanabe, M. (J. Am. Chem. Soc., 2014)

(untitled) - Fechler, N.; Fellinger, T.-P.; Antonietti, M. (Adv. Mater. (Weinheim, Ger.), 2013)

(untitled) - Iwanow, M.; Finkelmeyer, J.; Söldner, A.; Kaiser, M.; Gärtner, T.; Sieber, V.; König, B. (Chem. – Eur. J., 2017)

(untitled) - Xu, H.; Guo, J.; Suslick, K. S. (Adv. Mater. (Weinheim, Ger.), 2012)

(untitled) - Mazlan, M. A. F.; Uemura, Y.; Yusup, S.; Elhassan, F.; Uddin, A.; Hiwada, A.; Demiya, M. (Procedia Eng., 2016)

(untitled) - Tzvetkov, G.; Mihaylova, S.; Stoitchkova, K.; Tzvetkov, P.; Spassov, T. (Powder Technol., 2016)

(untitled) - Phiri, Z.; Everson, R. C.; Neomagus, H. W. J. P.; Wood, B. J. (J. Anal. Appl. Pyrolysis, 2017)

(untitled) - Dufour, A.; Celzard, A.; Fierro, V.; Martin, E.; Broust, F.; Zoulalian, A. (Appl. Catal., A, 2008)

(untitled) - Ahmadpour, A.; Do, D. D. (Carbon, 1996)

(untitled) - Mohammad-Khah, A.; Ansari, R. (Int. J. ChemTech Res., 2009)

(untitled) - Rodríguez-Reinoso, F.; Molina-Sabio, M.; González, M. T. (Carbon, 1995)

(untitled) - Kühl, H.; Kashani-Motlagh, M. M.; Mühlen, H.-J.; van Heek, K. H. (Fuel, 1992)

(untitled) - Lu, G. Q.; Do, D. D. (Carbon, 1992)

(untitled) - Tomków, K.; Siemieniewska, T.; Czechowski, F.; Jankowska, A. (Fuel, 1977)

(untitled) - DeGroot, W. F.; Richards, G. N. (Carbon, 1989)

(untitled) - Wu, M.; Zha, Q.; Qiu, J.; Guo, Y.; Shang, H.; Yuan, A. (Carbon, 2004)

Activated Carbon - Marsh, H.; Rodríguez-Reinoso, F. (Activation Processes (Chemical), 2006)

(untitled) - Fellinger, T.-P.; Thomas, A.; Yuan, J.; Antonietti, M. (Adv. Mater. (Weinheim, Ger.), 2013)

(untitled) - Skrabalak, S. E.; Suslick, K. S. (J. Am. Chem. Soc., 2006)

(untitled) - Atkinson, J. D.; Fortunato, M. E.; Dastgheib, S. A.; Rostam-Abadi, M.; Rood, M. J.; Suslick, K. S. (Carbon, 2011)

(untitled) - Yan, Y.; Zhang, F.; Meng, Y.; Tu, B.; Zhao, D. (Chem. Commun., 2007)

(untitled) - Romero-Anaya, A. J.; Ouzzine, M.; Lillo-Ródenas, M. A.; Linares-Solano, A. (Carbon, 2014)

(untitled) - Fuertes, A. B. (J. Mater. Chem., 2003)

(untitled) - Shin, Y.; Wang, L.-Q.; Bae, I.-T.; Arey, B. W.; Exarhos, G. J. (J. Phys. Chem. C, 2008)

(untitled) - Ryu, J.; Suh, Y.-W.; Suh, D. J.; Ahn, D. J. (Carbon, 2010)

(untitled) - Sun, X.; Li, Y. (Angew. Chem., Int. Ed., 2004)

(untitled) - Kazmierczak-Razna, J.; Nowicki, P.; Pietrzak, R. (Powder Technol., 2015)

(untitled) - Wang, T.; Tan, S.; Liang, C. (Carbon, 2009)

(untitled) - Ji, Y.; Li, T.; Zhu, L.; Wang, X.; Lin, Q. (Appl. Surf. Sci., 2007)

(untitled) - Lyubchik, S. B.; Benoit, R.; Béguin, F. (Carbon, 2002)

(untitled) - Wang, S.; Lu, G. Q. (Carbon, 1998)

(untitled) - Jaramillo, J.; Álvarez, P. M.; Gómez-Serrano, V. (Fuel Process. Technol., 2010)

(untitled) - Han, W.; Liu, H.; Zhu, H. (Catal. Commun., 2007)

(untitled) - Figueiredo, J. L.; Pereira, M. F. R.; Freitas, M. M. A.; Órfão, J. J. M. (Carbon, 1999)

(untitled) - Yang, G.; Chen, H.; Qin, H.; Feng, Y. (Appl. Surf. Sci., 2014)

(untitled) - de Clippel, F.; Dusselier, M.; Van de Vyver, S.; Peng, L.; Jacobs, P. A.; Sels, B. F. (Green Chem., 2013)

(untitled) - Chen, J.; Yang, J.; Hu, G.; Hu, X.; Li, Z.; Shen, S.; Radosz, M.; Fan, M. (ACS Sustainable Chem. Eng., 2016)

(untitled) - Singh, G.; Kim, I. Y.; Lakhi, K. S.; Srivastava, P.; Naidu, R.; Vinu, A. (Carbon, 2017)

(untitled) - Shafeeyan, M. S.; Daud, W. M. A. W.; Houshmand, A.; Arami-Niya, A. (Appl. Surf. Sci., 2011)

(untitled) - Moreno-Castilla, C.; Ferro-Garcia, M. A.; Joly, J. P.; Bautista-Toledo, I.; Carrasco-Marin, F.; Rivera-Utrilla, J. (Langmuir, 1995)

Handbook of Heterogeneous Catalysis - Sing, K. S. W.; Everett, D. H.; Haul, R. A. W.; Moscou, L.; Pierotti, R. A.; Rouquerol, J.; Siemieniewska, T. (Reporting Physisorption Data for Gas/Solid Systems, 2008)

(untitled) - Brunauer, S.; Emmett, P. H.; Teller, E. (J. Am. Chem. Soc., 1938)

(untitled) - Sing, K. (Colloids Surf., A, 2001)

(untitled) - Dubinin, M. M. (Carbon, 1989)

(untitled) - Barrett, E. P.; Joyner, L. G.; Halenda, P. P. (J. Am. Chem. Soc., 1951)

(untitled) - Setoyama, N.; Kaneko, K.; Rodriguez-Reinoso, F. (J. Phys. Chem., 1996)

(untitled) - Sethia, G.; Sayari, A. (Carbon, 2016)

(untitled) - Boehm, H. P. (Carbon, 2002)

(untitled) - Otowa, T.; Nojima, Y.; Miyazaki, T. (Carbon, 1997)

(untitled) - Srinivasakannan, C.; Zailani Abu Bakar, M. (Biomass Bioenergy, 2004)

(untitled) - Galiatsatou, P.; Metaxas, M.; Arapoglou, D.; Kasselouri-Rigopoulou, V. (Waste Manage. (Oxford, U. K.), 2002)

(untitled) - Nevskaia, D. M.; Santianes, A.; Muñoz, V.; Guerrero-Ruı́z, A. (Carbon, 1999)

(untitled) - Pevida, C.; Plaza, M. G.; Arias, B.; Fermoso, J.; Rubiera, F.; Pis, J. J. (Appl. Surf. Sci., 2008)

(untitled) - Ternero-Hidalgo, J. J.; Rosas, J. M.; Palomo, J.; Valero-Romero, M. J.; Rodríguez-Mirasol, J.; Cordero, T. (Carbon, 2016)

(untitled) - Dı́az-Terán, J.; Nevskaia, D. M.; Fierro, J. L. G.; López-Peinado, A. J.; Jerez, A. (Microporous Mesoporous Mater., 2003)

(untitled) - Guedidi, H.; Reinert, L.; Lévêque, J.-M.; Soneda, Y.; Bellakhal, N.; Duclaux, L. (Carbon, 2013)

(untitled) - Kumar, A.; Mohan Jena, H. (Appl. Surf. Sci., 2015)

Carbon Materials for Catalysis - Bitter, J. H.; de Jong, K. P. (Preparation of Carbon-Supported Metal Catalysts, 2008)

(untitled) - Van Dam, H. E.; Van Bekkum, H. (J. Catal., 1991)

(untitled) - Kim, K. T.; Chung, J. S.; Lee, K. H.; Kim, Y. G.; Sung, J. Y. (Carbon, 1992)

(untitled) - Pinna, F. (Catal. Today, 1998)

(untitled) - Gurrath, M.; Kuretzky, T.; Boehm, H. P.; Okhlopkova, L. B.; Lisitsyn, A. S.; Likholobov, V. A. (Carbon, 2000)

(untitled) - Corapcioglu, M. O.; Huang, C. P. (Carbon, 1987)

(untitled) - Radkevich, V. Z.; Senko, T. L.; Wilson, K.; Grishenko, L. M.; Zaderko, A. N.; Diyuk, V. Y. (Appl. Catal., A, 2008)

(untitled) - Toebes, M. L.; van Dillen, J. A.; de Jong, K. P. (J. Mol. Catal. A: Chem., 2001)